2016
DOI: 10.1016/j.reactfunctpolym.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Bio-based high performance epoxy-anhydride thermosets for structural composites: The effect of composition variables

Abstract: Please cite this article as: Adlina Paramarta, Dean C. Webster, Bio-based high performance epoxy-anhydride thermosets for structural composites: The effect of composition variables, (2016), AbstractThe structure-property relationships of a designed series of anhydride-cured epoxidized sucrose soyate (ESS) thermosets were studied. Epoxidized sucrose soyate is a novel bio-based epoxy resin derived from sucrose and soybean oil fatty acids, and it contains an average of 12 epoxy functional groups per molecule. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 40 publications
(48 reference statements)
0
35
0
Order By: Relevance
“…In addition, the width of the tan delta peak curvature might suggest the degree of homogeneity of the network. Paramarta et al and Pan et al also found the same pattern for bio-based thermosets, whereby a broader peak and a narrower peak was due to a higher catalyst amount in the blended polymer [2,34].…”
Section: Tan Delta δmentioning
confidence: 63%
See 1 more Smart Citation
“…In addition, the width of the tan delta peak curvature might suggest the degree of homogeneity of the network. Paramarta et al and Pan et al also found the same pattern for bio-based thermosets, whereby a broader peak and a narrower peak was due to a higher catalyst amount in the blended polymer [2,34].…”
Section: Tan Delta δmentioning
confidence: 63%
“…DMA revealed viscoelastic properties such as the glass transition temperature, the crosslink density, and the temperature dependence of the storage modulus, the loss modulus, and the tan delta of the epoxy and the jatropha bio-epoxy [2]. The graphs of the DMA test are shown in Figure 4 for Tan Delta, Figure 5 for Storage Modulus, and Figure 6 for Loss Modulus.…”
Section: Dynamic Mechanical Analysis Resultsmentioning
confidence: 98%
“…The lower reactivity of internal epoxies compared to terminal ones are well‐known in the literature, however, anhydrides are known to easily open these epoxy moieties . This is the reason why the epoxies were cured with 4‐methylcyclohexane‐1,2‐dicarboxylic anhydride (MHHPA), which is a common anhydride used in epoxy‐anhydride thermosets (Scheme ) . MHHPA was also chosen for its liquid state at room temperature, as it allows for a homogeneous system, whereas most anhydrides are solids at room temperature and thus the mixing process is highly complicated.…”
Section: Resultsmentioning
confidence: 99%
“…However, all of these triglycerides exhibit similar structures with long flexible chains which provide low thermal or mechanical properties induced by a low crosslinking density and T g . Recently, Webster et al have described the sucrose soyate, a new bio‐based epoxy monomer which contains a sucrose backbone, inducing high rigidity and T g to the final thermosets . However, aromaticity is highly desired in epoxy networks in order to confer high thermal and mechanical properties to the final materials.…”
Section: Introductionmentioning
confidence: 99%
“…According to NMR spectroscopic results the acryl/epoxy groups' ratio was at about 30/70% for both oils. It is noteworthy, that by contrast to epoxidation of plant oils, their subsequent acrylation is never complete 12,32 .…”
Section: Methodsmentioning
confidence: 99%